The XMM-Newton View of the Northern Disk of M31 - Sasaki, M.; Filipovic, M.; Haberl, F.; Hatzidimitriou, D.; Henze, M.; Kavanagh, P.; Long, K.; Plucinsky, P.; Williams, B. (2017)
The XMM-Newton survey of M31 revealed extended diffuse emission in the northern disk of M31, which is well correlated with the star-forming ring of the galaxy. The stellar population of this part of M31 has been extensively studied in the optical in the Panchromatic Hubble Andromeda Treasury (PHAT) survey. We have observed the northern disk of M31 in areas within the PHAT footprint in deep XMM-Newton pointings. We have thus obtained a map of the X-ray emission of the hot interstellar medium (ISM) in a spiral galaxy like our own on arcmin scales and a complete list of X-ray sources down to the confusion limit of a few 10^{34} erg/s, with variability and spectral information for most of the sources. We will present the first results of the study of the X-ray source population and that of the hot ISM.